2023
DOI: 10.1002/agg2.20331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two categorically differing emergent wetland plants on evapotranspiration

Abstract: Although wetlands are an important component of many landscapes, emergent plants have had variable impacts on wetland hydrology. In the present study, similar to what others have done with emergent plants, we investigated the impacts of black willow (Salix nigra Marshall) and Pennsylvania smartweed (Persicaria pensylvanica L.) on water loss from standing water relative to water loss with no emergent plants from 2018 to 2020. Pans were established with soil and standing water for three replications of five trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Some studies report (Roulet N.T and Woo M.K.,1986) this equality for a low arctic site, and a review of swamps/bogs (Linacre E.T.,1976) transpiration concluded rough equality with lakes is probably the most reasonable assumption. Studies by Jiménez-Rodríguez et al, 2019;Bois et al, 2021 andKiniry, 2023) have indicated that when comparing with open water evaporation, the plant type is important as some promote higher evapotranspiration than open water evaporation and some are equivalent.…”
Section: Area Of Tankmentioning
confidence: 99%
“…Some studies report (Roulet N.T and Woo M.K.,1986) this equality for a low arctic site, and a review of swamps/bogs (Linacre E.T.,1976) transpiration concluded rough equality with lakes is probably the most reasonable assumption. Studies by Jiménez-Rodríguez et al, 2019;Bois et al, 2021 andKiniry, 2023) have indicated that when comparing with open water evaporation, the plant type is important as some promote higher evapotranspiration than open water evaporation and some are equivalent.…”
Section: Area Of Tankmentioning
confidence: 99%